Soil Quality Indicators Associated With The Application Of Mycorrhizal Fungi In Coffee Plantations - Avila Bayona, Catherine Paola; Alvarez Cano, Maria Alejandra; Avellaneda Torres, Lizeth Manuela (Ingeniería Solidaria, 2020)
Introduction: This article is the result of the research work “Evaluation of the quality of the soil associated with the use of mycorrhizae in coffee plantations in the Municipality of Sasaima, Cundinamarca” carried out duringthe years 2018 and 2019 at the Universidad Libre.Problem: Several investigations report the use of mycorrhizal fungi in plant development, however, there are few studies regarding the relationship between mycorrhizae and soil quality indicators.Methodology: Four plots were evaluated, applying: 1) Control; 2) Local native mycorrhizae isolated by the authors; 3) Commercial liquid mycorrhizae; and 4) Commercial solid mycorrhizae. The samples of the rhizosphericsoils were taken and bimonthly monitoring was applied until 5 collection cycles were obtained. The physicochemical parameters, abundance of functional groups of microorganisms, and enzymatic activities ofthe soil were determined and analyzed by means of univariate and multivariate statistical analysis.Conclusion: The research hypothesis was validated since the mycorrhizae inoculation significantly increased the values of the soil quality indicators, namely organic carbon (14%), moisture (19%), phosphorus (30%), abundanceof nitrogen-fixing bacteria (5.5%), phosphate-solubilizing bacteria (7.8%), cellulolytic bacteria (9.3%), and phosphate-solubilizing fungi (2.6%). In addition, the local native mycorrhizae that were isolated by theauthors showed greater benefits than those of the commercial mycorrhizae.Originality: This research reveals the impact of mycorrhizae on the soil quality indicators over time during thefirst year of application, especially on the microbial and enzymatic parameters.Limitations: Several authors have investigated the importance of the mycorrhizae on the physicochemical parameters of the plant, and not on the microbial and enzymatic parameters of the soil.
Keywords: soil enzymes; functional groups of microorganisms; soil nutrients; organic farming